A New-fangled Corona virus coupled with Human Respiratory and AI in COVID-19 Discovery - et. al., V. A. Kotkar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Recently a very strange time to fight with invisible enemy. The Corona virus ailment 2019 also known as COVID-19 outburst, which emerged from Wuhan, the Hubei Province, China, had broaden to all the regions of China and 28 additional countries. Corona viruses are a group of viruses with non segmented, single stranded and positive–sense RNA genomes. Corona viruses is also popular to contaminate human hosts and effect respiratory disease like brutal SARS-CoV (Acute Respiratory Syndrome Corona virus) and MERS-CoV (Middle East Respiratory Syndrome Corona virus). In this paper we discussed on detail analysis of COVID-19 disease.